Edged Weapons and Ritualized Theatrical Performances in Iran - Elena I. Malozyomova (Историческое оружиеведение, 2020)
The article is devoted to the analyzes of number of Iranian edged weapons, lacking any fighting efficiency but distinctively ornamented, from the collections of the Russian museum of ethnography and Peter the Great Museum of anthropology and ethnography (the Kunstkamera). Such weapons of diversified types (sabers, swords, daggers, battle-axes, defensive weapons) form a considerable part of museum collections, and evidently were produced by quantities in Iran, from where they appeared in the museums either directly, that is important, or via the antique shops in Europe and Russia in the second half of the 19th-the beginning of the 20th centuries. Based on the complex analyses of both the objects, and primary sources as well as research literature on history and ethnography, the author puts these arms in the context of Iranian culture of the 19th century, linking their use with the rituals, organized in the first ten days of muharram, a month of the Muslim lunar year. During these days, various ceremonies, commemorating the martyrdom of the third shia imam Khusain in the desert near the city of Karbala in 680, take place in the shia Muslim communities. The author provides profound descriptions and analyses of the activities and performances, that could have incorporated such kind of non-battle arms and armour, specially made for these occasions, as well as the real weapons, thus acquiring another ethnographical status. Travelers, ethnographers, historians, who visited Iran and nearby territories with shia brand of islam venerated, described the ceremonies in details, through their attention was paid more to the scenario of the events, their religious and ethnic specificity, than to the objects used. Nonetheless, the analyses of philological data, cultic and ritual aspects of the ceremonies, and comparison of even a few facts from primary sources and juxtaposition them with the images, made by the artists who saw them with their own eyes, as well as with real objects, permitted the author to arrive at the steadfast conclusions. These are the principles of ornamentation of the arms and armor under discussion as well as the range of decorating them images, which as investigation has showed, reflect the symbolic ideas of muharram ceremonies and vivid in these events heroic and mythological features of Iranian culture, that have appeared to be one of the most important sources to determinate the place of these objects in the Iranian ritual culture of the second half of the 19th century and the beginning of the 20th. The stylistic analyses of such objects from the Russian museum of ethnography and Peter the Great Museum of anthropology and ethnography (the Kunstkamera), provided by the author, can serve as the basis for the attribution of this kind of weapons from other museums to the sub-culture of muharram ceremonies.